The Influence of HESQUAL on Student Image and Satisfaction: Implications for the Intention of Recommending The Universitas Islam Indonesia Study Program - Khusaini, Rayhan Aditya; Hartono, Arif (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research investigates the key factors that influence students' intention to stay at a university and their intention to recommend the university, especially in the context of Universitas Islam Indonesia. This research emphasizes the importance of the quality of university services in creating meaningful relationships between students and the university. The proposed research model tests the relationship between university service quality (HESQUAL), brand image, satisfaction, and their impact on student's intention to stay and recommend the university. The results of the analysis show that university service quality has a positive and significant influence on the university's brand image and student satisfaction. Apart from that, the university's brand image also has a positive and significant effect on student satisfaction. Student satisfaction, in turn, has a positive and significant influence on their intention to stay and recommend the university. This research provides important insights for universities in understanding the factors that influence student loyalty and recommendations.